An exploratory analysis of the role of social supports in psychiatric medication discontinuation: results related to family involvement. Issue 3 (3rd July 2019) - Ostrow, Laysha; Croft, Bevin; Weaver, Anne; Naeger, Sarah
ABSTRACT: Objective : Individuals in psychiatric treatment frequently choose to stop taking psychiatric medications, but little is known about the role of social supports in this process. Methods : This service user-led study of 194 adults who sought to completely discontinue prescribed psychiatric medications explores the role of various groups that may be a source of social support. Respondents who attempted to discontinue medication completed a web survey. We conducted bivariate and multivariate analyses to explore the relationship of social support to discontinuation. Results : Of all social support groups, only family was significantly associated with medication discontinuation. Respondents who rated family as helpful in the discontinuation process were less likely to completely discontinue than those who rated family as unhelpful or who reported no family involvement. Additionally, we observed a statistically significant but nonlinear relationship where respondents who rated their families as either "very supportive" or "very unsupportive" of the decision to discontinue were less likely to meet their original discontinuation goal than those with more neutral ratings. Discussion : The results of this study suggest families have an important and complex role in medication decision-making. Efforts to improve the quality of social networks should include family, as should future research.